Frederic J. Fleron, Jr., Erik P. Hoffmann, Robbin F. Laird (eds.), Classic Issues in Soviet Foreign Policy. From Lenin to Brezhnev, New York: Aldine de Gruyter, 1991, 349 s., DM 48,00; Frederic J. Fleron, Jr., Erik P. Hoffmann, Robbin F. Laird (eds.), Con - Nørgaard, Ole (Politica, 1992)
Frederic J. Fleron, Jr., Erik P. Hoffmann, Robbin F. Laird (eds.), Classic Issues in Soviet Foreign Policy. From Lenin to Brezhnev, New York: Aldine de Gruyter, 1991, 349 s., DM 48,00; Frederic J. Fleron, Jr., Erik P. Hoffmann, Robbin F. Laird (eds.), Contemporary Issues in Soviet Foreign Policy. From Brezhnev to Gorbachev, New York: Aldine de Gruyter, 1991, 520 s., DM 54,00.